Editorial Comments - Marie Poggenpoel (AOSIS, 1998)
We are experiencing an exciting time in health education, practice and research in south Africa. Opsomming Ons beleef 'n opwindende tyd in gesondheidsonderring, -praktyk en -navorsing in Suid-Africa. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.